2021
DOI: 10.52380/ijpes.2021.8.2.403
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Mathematical Thinking Levels of Individual and Team Athletes in Terms of Different Variables

Abstract: This study was carried out to examine athletes' mathematical thinking levels who do individual and team sports in different variables. The study was conducted with a relational screening model, which is one of the general screening models. The data were collected by a survey method. "Mathematical Thinking Scale" was used to determine the mathematical thinking levels of athletes. The research population was composed of licensed athletes studying in high schools and universities in the 2020-2021 academic year in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Thinking can be interpreted as an effective, functional, and directed action. According to contemporary psychologists (Nedim et al, 2021), thinking starts with problems. So it can be concluded that the thinking process is the ability to determine the solution to a problem, thus the thinking process begins with the problem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thinking can be interpreted as an effective, functional, and directed action. According to contemporary psychologists (Nedim et al, 2021), thinking starts with problems. So it can be concluded that the thinking process is the ability to determine the solution to a problem, thus the thinking process begins with the problem.…”
mentioning
confidence: 99%
“…Not every way of thinking is mathematical, but the contribution of mathematical thinking in problem solving is undeniable. Mathematical thinking defines how an individual prefers to understand, think, and present mathematical facts and connections with certain internal images or external representations (Nedim et al, 2021). In other words, mathematical thinking is the investigative process one goes through when solving a problem.…”
mentioning
confidence: 99%